2022
DOI: 10.3390/cancers14143519
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Targeted Antibody–Drug Conjugates Display Potent Antitumor Activities in Preclinical Extramammary Paget’s Disease Models: In Vivo and Immunohistochemical Analyses

Abstract: Extramammary Paget’s disease (EMPD) is an adenocarcinoma that develops mainly in the genital region of older adults. The prognosis for advanced EMPD is almost always poor; thus, novel therapeutic strategies need to be developed. HER2-targeted antibody–drug conjugates (ADCs) such as trastuzumab emtansine and trastuzumab deruxtecan have proven effective against HER2-positive breast cancers; however, no studies have addressed HER2-targeted ADCs as treatments for EMPD. We examine the efficacy of ADCs against an EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A recent in vivo study demonstrated that HER2 over-expression was more frequent in patients with invasive EMPD than in those with in situ or microinvasive EMPD. Treatment with T-DXd or T-DM1 was found to eradicate an EMPD patientderived xenograft model with no recurrence observed after 10 weeks (24). HER2-targeted ADCs may be promising treatment options for patients with ERBB2-mutant or HER2-over-in vivo 37: 2618-2627 (2023) 2623 In addition, genomic and immunohistochemical profiling has revealed that the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) is frequently mutated in EMPD, and the androgen receptor (AR) is over-expressed in the majority of the cases (37,38).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent in vivo study demonstrated that HER2 over-expression was more frequent in patients with invasive EMPD than in those with in situ or microinvasive EMPD. Treatment with T-DXd or T-DM1 was found to eradicate an EMPD patientderived xenograft model with no recurrence observed after 10 weeks (24). HER2-targeted ADCs may be promising treatment options for patients with ERBB2-mutant or HER2-over-in vivo 37: 2618-2627 (2023) 2623 In addition, genomic and immunohistochemical profiling has revealed that the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) is frequently mutated in EMPD, and the androgen receptor (AR) is over-expressed in the majority of the cases (37,38).…”
Section: Discussionmentioning
confidence: 94%
“…Although the prognosis of noninvasive EMPD is favorable (24), once metastasis occurs, the prognosis worsens (25). Some chemotherapeutic regimens have been proposed for metastatic EMPD; however, no standardized treatments have been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Paget cells were round to columnar with an increased nuclear/cytoplasmic (N/C) ratio and vacuolated cytoplasm. Since HER2 is frequently expressed in genital and anal EMPD (15-60% of cases) [8], a cell block was set-up with residual cellularity and HER2 expression explored by immunocytochemistry in four cases in order to support the diagnosis (Figure 3).…”
Section: Cytologymentioning
confidence: 99%